Mobility Engineering Proceedings of CAETS 2015 Convocation on Pathways to Sustainability - Tandon, Mahesh Chandra; Ghosh, Purnendu; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
The book contains the proceedings of CAETS 2015 Convocation on 'Pathways to Sustainability: Energy, Mobility and Healthcare Engineering' that was held on October 13-14, 2015 in New Delhi. This 3 volume proceedings provide an international forum for discussion and communication of engineering and technological issues of common concern. This volume talks about 'Mobility' and includes 14 chapters on diverse topics like creating sustainable transportation systems, mobility of the future, unique engineering features like Delhi metro, digitally re-imagining mobility, trends and future strategies of transportation electrification, etc. The contents of this book will be useful to researchers, professionals, and policy makers alike.
Chapter 1. Renaissance and Electric Vehicles Development -- Chapter 2. Smart Mobility: Driver State Estimation and Advanced Driver-vehicle Interfaces -- Chapter 3. Modular Hydraulic Trailer Technology -- Chapter 4. Current Situation and Prospect of Transportation Development in China -- Chapter 5. Civil Engineering Innovation Shaping Mobility of the Future -- Chapter 6. Future Shapes of Bridges in Urban Environment -- Chapter 7. Making of Bandra-Worli Sea Link -- Chapter 8. Digitally Reimagining Mobility -- Chapter 9. Willingness to Pay for Improvement in Service Quality of Public Transit System -- Chapter 10. Shinkansen/High Speed Railway -- Chapter 11. Unique Engineering Features of Delhi Metro -- Chapter 12. Creating Sustainable Transportation System in India - Materials Engineer Perspective -- Chapter 13. Lack of Enforcement Nullifies the Benefits of Mobility Improvement Measures: Some Examples -- Chapter 14. Optimizing Traffic Control for a Minimization of Fuel Consumptions and Emission Values.
Keywords: Transportation engineering; Traffic engineering; Transportation Technology and Traffic Engineering